(Re)Framing ocean acidification in the context of the United Nations Framework Convention on Climate Change (UNFCCC) and Paris Agreement. (26th November 2019) - Harrould-Kolieb, Ellycia R.
ABSTRACT: Ocean acidification is most frequently framed by the scientific community as a concurrent threat to climate change, rather than an effect of it. This separation of the two phenomena has long been deemed as a way of garnering heightened policy attention for ocean acidification rather than having it bound up in the often contested politics of climate change. This effort, however, appears to have resulted in the inadvertent placing of ocean acidification outside of the mandate of the United Nations Framework Convention on Climate Change (UNFCCC). This has created a significant gap in the global governance of this issue with no multilateral agreement understood as having jurisdiction over the mitigation of rising ocean acidity. For these reasons this paper argues that an alternative framing of ocean acidification as an effect of climate change is warranted. This would include ocean acidification in the core obligations of the Convention, thereby filling the mitigation governance gap and avoiding perverse implementation outcomes. It is contended that interpreting the UNFCCC in this way is more consistent with its objective and purpose than the existing interpretations that place ocean acidification beyond the remit of the Convention. Key policy insights Ocean acidification is best understood as an effect of climate change in the context of the UNFCCC, and therefore is included in its obligations to combat climate change and its adverse effects. An obligation to address ocean acidification has implications for the way that the provisions of the Convention, particularly on mitigation, are implemented. Mitigation activities that exacerbate ocean acidification or lead to emission reduction pathways that do not prevent dangerous acidification should be deemed inconsistent with the Convention. Protection, conservation and restoration of coastal and marine ecosystems should become a priority area for action within the UNFCCC.